Anchoring of atmospheric teleconnection patterns by Arctic Sea ice loss and its link to winter cold anomalies in East Asia. (27th May 2020) - Li, Muyuan; Luo, Dehai; Simmonds, Ian; Dai, Aiguo; Zhong, Linhao; Yao, Yao
Abstract: In this paper, the physical processes underlying recent winter cold anomalies over East Asia (EA) are examined via statistical analysis. It is found that the EA cold anomaly depends on the warming in the North Atlantic, sea ice loss in the Barents–Kara Sea (BKS), and atmospheric teleconnection patterns. Specifically, the sea ice loss in the BKS can anchor teleconnection patterns originating from different North Atlantic sea surface temperature (SST) patterns. Different patterns of North Atlantic warming can affect the position of the cold anomaly region through altering the atmospheric circulations. In addition, whether the relevant teleconnection pattern leads to enhanced cold anomaly over EA crucially depends on the sea ice loss in the BKS, because it can anchor the blocking anticyclone embedded in the teleconnection pattern over the Ural region and make it more persistent and quasi‐stationary. Furthermore, it is found that the role of SST modes in the EA cold anomaly depends on their time scales. Although the strong basin‐scale warming (north–south SST tripolar mode) in the North Atlantic mid‐ to high‐latitudes plays a major role in decadal (interannual) cold anomaly over EA, it appears that the Atlantic east–west SST dipole structure dominates winter temperature variations over EA in recent decades on both the interannual and decadal time scales. Abstract : This is the graphical abstract of Anchoring of atmospheric teleconnection patterns by Arctic sea ice loss and its link to winter cold anomalies in East Asia, authored by M. L., D. L., I. S., A. D., L. Z. and Y. Y. It is found that the winter cold anomalies over East Asia is related to both different SST modes in the North Atlantic via teleconnection patterns on both interannual and decadal time‐scales and the decrease in sea ice extent in the Barents–Kara Sea by anchoring the blocking anticyclone.